Comparison of Learning Outcomes Between Using PBL And TAI Viewed From Student’s Motivation - Dwi Oktaviani Ogara; Suyanto (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
This study aims to find out: (1) the differences of learning outcomes between student’s learning by using PBL model and student’s who learn to use TAI model, (2) the difference of the learning outcome between the use of PBL model and TAI model at learners who have high learning motivation, (3) the difference of the learning outcome between the use of PBL model and TAI model at learners who have low learning motivation and (4) the interaction effect between of learning models and student’s motivation to learning outcomes. This was a quasi-experimental research study employing the factorial 2x2 design. The research population is the XI grade social class of SMA Negeri 1 Ngaglik, totaling 94 student's. The sample was selected using simple random sampling technique. The data analysis used the variant analysis (Anava) two way with significance level of (ɑ) 0.05.